“Relações de alteridade, segregação e degradação urbanas em São Paulo: uma análise dos efeitos simbólicos da presença de segmentos populacionais étnicos estigmatizados na "vizinhança‟ - Cunha, Moisés de Freitas (2016)
This work aims to analyze issues as HOUSING and NEIGHBORHOOD5 in São Paulo, having as core concepts the presence of ethnic and symbolic (psychic income6, for instance) factors for the assessing of urban degradation. In other terms, how the presence of people considered “outsiders” (ELIAS & SCOTSON, 2000) can influence and impact the decisions of “established” ones as per the acquisition and/or maintenance of real estate, resulting in the (de)valuation of housing entrepreneurship. It also proposes the analysis of the attitudes towards “outsiders”, as per stigmas (“Culture of Poverty”) and ideologies of domination “...racial segregation as essential to the maintenance of racial supremacy...” (HARRIS, 2003), as those imposed after the second half of the XIX century, according to Norbert Elias, Erving Goffman and Oscar Lewis, respectively. It also aims to test the “Thomas Theorem”7 as a possible explaining axis for the understanding of sources of stigma and prejudice against people seen as “outsiders” in modern cities. Starting from a case study of a vertical condominium in the borough “Belém” in São Paulo city, interviews with dwellers were carried out to apprehend the meaning of the attitudes of alterity/urban degradation. This study also aims to better think and, if possible, propose corrective approaches, either collective or individual, almost under the terms of Habermas in “emancipatory fragments”, or even by means of Jean Paul Sartre approach, i.e.: “it doesn‟t matter what was done to me, what matters is what I do with what was done to me…”